Penerapan Metode Pembelajaran Resitasi Dalam Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Fiqih Kelas VII C di MTs Darul Ulum Sukaraja Kecamatan Logas Tanah Darat Kabupaten Kuantan Singingi - Iis Kurniati; Bustanur Bustanur; Alhairi Alhairi (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2022)
The learning outcomes of class VII C students in fiqh subjects at MTs. Darul Ulum Sukaraja are still relatively low, this is evidenced by the existence of student scored that are still below the specified KKM (70), therefore learning methods are needed that can improve learning outcomes student. One method that can improve student learning outcomes is the resifast learning method restast learning. This study aims to determine whether there is an increase in student learning outcomes in class VII C fiqh subjects at MTs. Darul Ulum Sukaraja, Logas Tanah Darat District, Kuantan Singingi Regency. With using data collection techniques through observation, interview and documentation. This research was carried out in 3 cycles, this was done so that the authors could see student learning outcomes by applying the method restast learning. The method used in this study is the resist learning method, where this method requires students to make using their own sentences. Based on the results of data analysis, research has increased starting from pre-action (pre-cycle) 71,36%, Cycle 1 75,23%, Cycle II 78,09% and Cycle III 87,19%. So it can be concluded that the application of the tast learning method in improving results student learning in the subjects of fiqh class VII C at MTs. Darul Ulum Sukaraja, Logas Tanah Darat Diistrict. Kuantan Singingi Regency can improve learning outcomes